1997
DOI: 10.1089/dna.1997.16.281
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Expression of an Isoform of Human CDP-Diacylglycerol Synthase cDNA

Abstract: Phosphatidic acid (PA) is a phospholipid involved in signal transduction and in glycerolipid biosynthesis. CDP-diacylglycerol synthase (CDS) or CTP:phosphatidate cytidylyltransferase (EC 2.7.7.41) catalyzes the conversion of PA to CDP-diacylglycerol (CDP-DAG), an important precursor for the synthesis of phosphatidylinositol, phosphatidylglycerol, and cardiolipin. We describe in this study the isolation and characterization of a human cDNA clone that encodes amino acid sequences homologous to Escherichia coli, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 24 publications
(31 reference statements)
0
33
0
Order By: Relevance
“…Early studies described two CDS activities: one associated with the outer surface of the ER (95) and another located in the matrix of mitochondria that was responsible for feeding into cardiolipin synthesis (1360). Mammalian CDS enzymes have been cloned (589, 1325,1688), and two, highly similar but different genes, cds1 and cds2 are found in the human and other mammalian genomes (552,1645). Both CDS proteins localize to the ER, but they do not enter the PIS positive mobile compartment (796).…”
Section: Phosphatidylinositol Synthesismentioning
confidence: 99%
“…Early studies described two CDS activities: one associated with the outer surface of the ER (95) and another located in the matrix of mitochondria that was responsible for feeding into cardiolipin synthesis (1360). Mammalian CDS enzymes have been cloned (589, 1325,1688), and two, highly similar but different genes, cds1 and cds2 are found in the human and other mammalian genomes (552,1645). Both CDS proteins localize to the ER, but they do not enter the PIS positive mobile compartment (796).…”
Section: Phosphatidylinositol Synthesismentioning
confidence: 99%
“…CDS genes have been identified from a series of eukaryotic organisms: yeast [30], fly [31], P. falciparum [32], mouse [33], and human [34][35][36]. CDS homologues are present in all eukaryotic genomes sequenced to date (Fig.…”
Section: Cdp-diacylglycerol Synthetases (Cdss)mentioning
confidence: 99%
“…Experiments by Weeks et al [34] suggested that even modest overexpression of human CDS1 levels amplifies cellular signaling systems. Drosophila mutants defective in the CDS isoform expressed in the photoreceptor cannot sustain a light-activated current due to rapid depletion of PtdIns-4,5-bisphosphate [31].…”
Section: Cdp-diacylglycerol Synthetases (Cdss)mentioning
confidence: 99%
“…To address this point, we tested the effect of a human CDP-DAG synthase, isolated from a leukocyte cDNA library, on the transcription of the above genes. GAL1 promoter-controlled overexpression of this gene complements the growth phenotype of the yeast cds1 mutant (26). However, CDP-DAG synthase activity is only 20 -30% of the wild type yeast level, resulting in inositol excretion even in the induction medium.…”
Section: Fig 2 Cdp-dag Ps and Pi Synthase Activities As A Functiomentioning
confidence: 98%